Effects of wine and grape polyphenols on blood pressure, endothelial function and sympathetic nervous system activity in treated hypertensive subjects. (December 2016) - Greyling, Arno; Bruno, Rosa M.; Draijer, Richard; Mulder, Theo; Thijssen, Dick H.J.; Taddei, Stefano; Virdis, Agostino; Ghiadoni, Lorenzo
Highlights: Study of blood pressure effects of wine and grape phenols in treated hypertensives. Treated hypertensives received no additional blood pressure lowering benefit from wine-grape polyphenol supplementation. Wine/grape polyphenols may potentially attenuate autonomic reactivity to stress. Abstract: In a randomized double-blind crossover trial, the effect of 8 week supplementation with grape and wine polyphenols on functional and structural vascular parameters and autonomic activity was evaluated in 40 essential hypertensive patients treated with diuretic monotherapy. Ambulatory blood pressure, brachial artery flow mediated dilation (FMD) and pulse-wave velocity (PWV) were measured at baseline and after each 8-week intervention. Forearm resistance artery endothelial function and muscle sympathetic nerve activity (MSNA) response to mental stress and cold-pressor test were measured in two separate sub-groups. No statistically significant differences were found across time or between groups in either blood pressure, FMD, PWV, or resistance artery endothelial function. The MSNA response to the two stressors was non-significantly attenuated after grape-wine polyphenol supplementation. These results do not support the hypothesis that daily consumption of a high dose of grape and wine polyphenols lowers blood pressure or affects vascular function in patients already on antihypertensive medication.